Comunicação e mobilização social para o desenvolvimento sustentável em assentamentos rurais em Bituruna (Paraná) - Pichelli, Katia Regina (2007)
This dissertation has like its aim to analyze the communications role in the process of mobilization and transfer of environmental and forest technologies oriented to build sustainable development in rural settlements. The methodology used is the Case Study in a qualitative way, through direct observation, and has like its theoretical basis the Social Mobilization Theory from Bernardo Toro e Nísia Werneck (2004). The research used observation and interviews with extension agents and settled people in Bituruna (Paraná). They were asked about roles and levels of communication: micro (personal), macro (segmented public) and mass (media in general). This study shows the importance of communication and its tools to improve the process of technology transfer among settled people and extension agents. It also reveals the natural challenges of the communication process, besides the necessity of creating mechanisms to stimulate collective participation like something that can transform settled people in actors of their development. Therefore, it shows that communication can be better used in the mobilization process and must be inserted in the settlements working plans, in a dialogic and participative perspective. The communication can so create sense, build imaginaries to be achieved and effectively mobilize to sustainable development.(AU)